Learners’ Attitudes towards using Communicative Approach in Teaching English at Wolkite Yaberus Preparatory School - Geza Nisrane, Dr. Tiglu; Dengela, Senbeta Tadesse (International Journal of English Literature and Social Sciences (IJELS), 2019)
This study was to explore the learners' attitude towards using the communicative approach in teaching English at Wolkite Yaberus Preparatory School in terms of their behavioral, cognitive and emotional aspects. To achieve the objectives of the study, a descriptive survey method was used and mixed method approach was employed to collect and analyze data. Under mixed method approach, sequential exploratory strategy was used and the data were gathered through questionnaires, interviews and classroom observation. The findings of the study revealed that the students in the study area have positive attitudes towards the communicative approach. However, they are not enthusiastic to participate in pairs or groups. The study further revealed that students perceive CLT as an effective learning approach and perceive most of the principles, goals, learner’s role, features and advantages to improve their language performance. Finally, based on the implication of the findings, recommendations were made for language teachers, curriculum designers and bodies concerned.